2012
DOI: 10.1021/jo301007x
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Diversification of a Cardiac Glycoside, Lanatoside C, by Organocatalysis

Abstract: Acylation of lanatoside C in the presence of organocatalyst 5 gave the C(4'''')-O-acylate in up to 90% regioselectivity (catalyst-controlled regioselectivity). Various functionalized acyl groups can be introduced at the C(4'''')-OH by a mixed anhydride method in the presence of 5 or the related organocatalyst. On the other hand, DMAP-catalyzed acylation of lanatoside C gave the C(3'''')-O-acylate in up to 97% regioselectivity (substrate-controlled regioselectivity). Thus, diverse regioselective introduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…We previously proposed a possible mechanism for the highly selective monoacylation of polyol compounds, [18][19][20][21][22][23][24][25][26][27] involving hydrogen bonding between the amide oxygen of catalyst 6 and the relatively acidic hydroxy group of the substrate. We therefore suspected that the C-7-allylic alcohol may take a hydrogen bond with the amide group of catalyst 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously proposed a possible mechanism for the highly selective monoacylation of polyol compounds, [18][19][20][21][22][23][24][25][26][27] involving hydrogen bonding between the amide oxygen of catalyst 6 and the relatively acidic hydroxy group of the substrate. We therefore suspected that the C-7-allylic alcohol may take a hydrogen bond with the amide group of catalyst 6.…”
Section: Resultsmentioning
confidence: 99%
“…catalyst 6, which was effective for the site-selective monoacylation of polyol compounds such as glycopyranoses, [18][19][20][21][22][23][24] linear diols, 25) tri-and tetra-substituted α,α′-alkenediols, 26,27) 2-aminopentane-1,5-diol derivatives, 28) and 10-deacetylbaccatin III. 29) The amide oxygen of catalyst 6 acted as a Brøn-sted base to allow hydrogen bonding with the relatively acidic hydroxy group of the substrate, thus inducing selective acylation of the adjacent hydroxy group.…”
Section: This Article Is Dedicated To Professor Satoshi ōMura In Celementioning
confidence: 99%
“…Under these backgrounds, we have developed a method for a non-enzymatic site-selective acylation of polyol compounds such as natural glycosides catalyzed by 4-dialkylaminopyridine-type nucleophilic organocatalyst 6 and the derivatives [5][6][7][8][9][10] ( Fig. 1).…”
Section: )mentioning
confidence: 99%
“…This siteselectivity seems independent from the intrinsic reactivity of 5 itself, because 4-dimethylaminopyridine (DMAP)-catalyzed acylation provided the corresponding 3⁗-O-acylate in 97% site-selectivity. 8) Thus, introduction of the acyl group at the C(4⁗)-OH was performed by catalyst-controlled manner and that at C(3⁗)-OH was done by substrate-controlled manner. In the course of our continuous efforts for site-selective diversification of polyol natural products, we found that catalyst 6 promoted highly site-selective acylation of 10-deacetylbaccatin III (1) at the C(10)-OH, which is a natural terpenoid available in relatively abundant amount and used as a key intermediate for clinically widely used antitumor agents, taxol (4) and taxotere (3) (Fig.…”
Section: )mentioning
confidence: 99%
“…2). For example, site-selective acylation of lanatoside C (5) took place at the C(4⁗)-OH in 86% site-selectivity among eight hydroxy groups in the different micro environments in the presence of catalyst 1 14) (Fig. 2).…”
Section: )mentioning
confidence: 99%